Towards 2015 : Spending for Indonesia's Development, Shaping the Prospects of a Middle-Income Country - World Bank (Washington, DC, 2013)
This report discusses the future of Indonesia's public expenditures as it enters the 21st century. It contributes to the discussion on Indonesia's spending priorities for the years ahead. These choices will impact the lives of Indonesians, and their opportunities to grow richer and receive better services. The report will contribute to Indonesia s next five-year plan, the RPJM, which will take effect in January 2010. Indonesia has been one of the most successful countries in reducing its debt-to-GDP ratio. Since 1999, when debt levels reached over 90 percent of GDP, Indonesia has reduced its debt levels to just above 30 percent of GDP by the end of 2008. Education spending increased from 11 percent of total government spending in 2001 to 15 percent in 2008. Chapter 1 discusses public spending from 2001 to 2009, including discretionary spending, key sectors, subsidies and decentralization. Chapter 2 analyzes Indonesia's economy in the current (2009) economic downturn. Indonesia is in a position of relative economic strength despite the impact of the global financial crisis. This is largely thanks to its broad-based growth that has avoided over-reliance on exports. The share of output that Indonesia exports is the smallest of the major Southeast Asian economies. Chapter 3 presents the future of Indonesia's fiscal growth to 2015. Notwithstanding noteworthy achievements over the past decade, Indonesia continues to face significant economic and social challenges, and major gaps remain in many areas of public expenditure. However, sustained fiscal consolidation and governance reforms, as well as resilience in the face of the global crisis, leave Indonesia well placed to push forward with sustained poverty reduction. Strategic use of public resources and continued growth could see swift improvement in economic and social outcomes over the coming five years.